Accident Experience of Civilian Pilots with Static Physical Defects - Dille, J Robert; Booze, Charles F (Canadian Journal of Optometry, 1980)
US study indicates that pilots with certain visual deficiencies had significantly more accidents than were expected on the basis of the observed-to expected ratio.